The public health implications of gentrification: tick‐borne disease risks for communities of color. Issue 4 (10th August 2022) - Halsey, Samniqueka J; VanAcker, Meredith C; Harris, Nyeema C; Lewis, Kaleea R; Perez, Lisette; Smith, Genee S
Abstract : Gentrification operates as a social driver of health that can increase tick‐borne disease (TBD) risk for communities of color through either population displacement or land‐use change. Research on the emergence of TBDs in urban environments has primarily focused on the ecological processes of urban landscapes that facilitate favorable habitats for host reservoirs and tick vectors. However, neglecting to view infectious disease risk from a socioecological framework will continue to result in policies and planning that disadvantage communities of color. Using Lyme disease as a case study, we integrated elements of environmental epidemiology, ecology, public health, and urban planning to propose pathways of gentrification as a socioecological process with public health implications. By drawing connections between urban ecology, urban planning, and environmental racism, we seek to bring awareness to disease ecologists, policy makers, and public health managers on the potential role of gentrification as a driver of tick‐borne pathogen exposure. Front Ecol Environ 2022;